Ate Complexes in Iron‐Catalyzed Cross‐Coupling Reactions. Issue 44 (28th September 2016) - Parchomyk, Tobias; Koszinowski, Konrad
Abstract: Iron‐catalyzed cross‐coupling reactions have an outstanding potential for sustainable organic synthesis, but remain poorly understood mechanistically. Here, we use electrospray‐ionization (ESI) mass spectrometry to identify the ionic species formed in these reactions and characterize their reactivity. Transmetalation of Fe(acac)3 (acac=acetylacetonato) with PhMgCl in THF (tetrahydrofuran) produces anionic iron ate complexes, whose nuclearity (1 to 4 Fe centers) and oxidation states (ranging from −I to +III) crucially depend on the presence of additives or ligands. Upon addition of i PrCl, formation of the heteroleptic Fe III complex [Ph3 Fe( i Pr)] − is observed. Gas‐phase fragmentation of this complex results in reductive elimination and release of the cross‐coupling product with high selectivity. Abstract : Iron up close and personal : Analysis of iron‐catalyzed cross‐coupling reactions by electrospray‐ionization mass spectrometry finds a multitude of anionic organoferrate complexes covering a remarkable range of different oxidation states. Gas‐phase fragmentation experiments afford in‐depth insight into the reactivity of these elusive species.